THE INFLUENCE OF WILLINGNESS TO PAY ON THE PRODUCTIVITY OF BREBES TYPICAL GIFT MERCHANTS - Hilda Kumala Wulandari; Dumadi Dumadi; Hendri Sucipto; Slamet Bambang Riono; Titi Rahmawati (Jurnal Ekonomi, 2022)
The strategic location makes Brebes a good economic center, especially for buying and selling souvenirs, as well as being a center for trading Brebes souvenirs. These were merchants with typical Brebes, totaling 34 merchants. The study used randomly distributed questionnaires. The data analysis method uses SPSS and is processed to calculate validity tests, reliability tests, normality tests, regression analysis, t tests, F tests and determination tests. The results showed that willingness to pay affects the productivity of typical Brebes souvenirs.